Comparison of Clinical Outcomes between Single- and Multiple-Perforator-Based Free Thoracodorsal Artery Perforator Flaps: Clinical Experience in 87 Patients - Karaaltin, Mehmet Veli; Erdem, Adnan; Kuvat, Samet; Cavdar, Gunay; Kerem, Hakan; Baghaki, Semih; Canter, Halil Ibrahim; Ozdemir, Azimet (My University, 2011)
Background: Although thoracodorsal artery perforator flaps have not gained popularity in the reconstructive era, the results of recent studies regarding the vascularity of thoracodorsal artery perforator flaps are promising. In the present study, the authors aimed to determine the clinical outcomes of free multiple-perforator versus single-perforator thoracodorsal artery perforator flaps.